Citizens' Opinions of and Experiences with Government Responses to COVID-19 Pandemic in Vietnam - Huyen Thanh Do; Cuong Viet Nguyen; Long Thanh Nguyen; Phuong Minh Nguyen; Quyen Ha Ngo; Quyen Ha Phung (Global Labor Organization (GLO), 2021)
The study aims to understand the impact of COVID-19 on citizens' livelihoods, the accessibility and effectiveness of the Government's relief packages, and public confidence and trust in the government responses to the pandemic. The study reveals several important findings as follows. First, the government responses to contain the COVID-19 outbreak have proved to be swift and effective, according to citizens surveyed. This is evident in the respondents' high consensus of strong support for government policy and actions to contain the pandemic. Importantly, people who have positive experiences with their provincial performance in governance and public administration were more supportive of the government's responses during the pandemic. Second, despite such government and citizen responses, the COVID-19 pandemic has generated negative impacts on the Vietnamese citizens and the national economy as a whole. The survey findings reveal that 24 percent of the respondents reported job losses because of the pandemic. These are also 65 percent of the respondents reporting income loss. Third, the findings of the survey reaffirm an overall positive feedback from citizens of and experience with the government's support package. People who received supports from the package were more likely to support the government's responses to the COVID-19 pandemic.
Keywords: 330; COVID-19; government's responses; aid package; economic impact